Photopolymerized Features via Beam Pen Lithography as a Novel Tool for the Generation of Large Area Protein Micropatterns. Issue 13 (4th February 2022) - Zhang, Xinpeng; Ding, Shaowei; Magoline, Jared; Ivankin, Andrey; Mirkin, Chad A.
Abstract: A cantilever‐free scanning probe lithography (CF‐SPL)‐based method for the rapid polymerization of nanoscale features on a surface via crosslinking and thiol‐acrylate photoreactions is described, wherein the nanoscale position, height, and diameter of each feature can be finely and independently tuned. With precise spatiotemporal control over the illumination pattern, beam pen lithography (BPL) allows for the photo‐crosslinking of polymers into ultrahigh resolution features over centimeter‐scale areas using massively parallel >160 000 pen arrays of individually addressable pens that guide and focus light onto the surface with sub‐diffraction resolution. The photoinduced crosslinking reaction of the ink material, which is composed of photoinitiator, diphenyl(2, 4, 6‐trimethylbenzoyl) phosphine oxide, poly(ethylene glycol) diacrylate, and thiol‐modified functional binding molecules (i.e., thiol‐PEG‐biotin or 16‐mercaptohexanoic acid), proceeds to ≈80% conversion with UV exposure (72 mW cm −2 ) for short time periods (0.5 s). Such polymer patterns are further reacted with proteins (streptavidin and fibronectin) to yield protein arrays with feature arrangements at high resolution and densities controlled by local UV exposure. This platform, which combines polymer photochemistry and massive arrays of scanning probes, constitutes a new approach to making biomolecular microarrays in a high‐throughput and high‐yielding manner, opening new routes for biochip synthesis, bioscreening, and cell biology research. Abstract : Beam pen lithography is utilized to synthesize arbitrary bioactive photopolymer arrays with nanoscale resolution on a surface via photopolymerization and thiol‐acrylate reactions. This high‐throughput scanning probe method allows for the spatiotemporal control over the polymer architectures using piezoactuator control and individually addressable pens, wherein the nanoscale position, scaffold morphology, and protein density can be finely and independently tuned.